2023
DOI: 10.3847/1538-4357/acb04e
|View full text |Cite
|
Sign up to set email alerts
|

How Nonlinearity Changes Different Parameters in the Solar Corona

Abstract: We consider different velocity amplitudes of incident waves to study nonlinearity effects on the plasma parameters around a magnetic null point in the solar corona. This could query the seismological methods used to observe and interpret damping profiles of oscillations of magnetic structures, based on linear theory. To this end, initially symmetric fast magnetoacoustic waves with three different amplitudes are applied to the system to pursue the effect of nonlinearity on the resulting plasma heating and flows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Studies have shown, through the use of magnetic field extrapolations from magnetogram observations, that magnetic null points are ubiquitous within the solar atmosphere (e.g., Longcope 2005;Régnier et al 2008). Due to this ubiquity, multiple studies have been made on the role of null points, in particular how they interact with the motion of magnetohydrodynamic (MHD) waves through wave propagation (e.g., McLaughlin & Hood 2004, 2005, 2006aMcLaughlin et al 2011;Sabri et al 2022Sabri et al , 2023 and mode conversion (e.g., McLaughlin & Hood 2006b;Thurgood & McLaughlin 2012;Tarr & Linton 2019;Pennicott & Cally 2021;Yadav et al 2022), but also as sources of slow, fast, and Alfvén waves (e.g., Lynch et al 2014;Karpen et al 2017;Thurgood et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown, through the use of magnetic field extrapolations from magnetogram observations, that magnetic null points are ubiquitous within the solar atmosphere (e.g., Longcope 2005;Régnier et al 2008). Due to this ubiquity, multiple studies have been made on the role of null points, in particular how they interact with the motion of magnetohydrodynamic (MHD) waves through wave propagation (e.g., McLaughlin & Hood 2004, 2005, 2006aMcLaughlin et al 2011;Sabri et al 2022Sabri et al , 2023 and mode conversion (e.g., McLaughlin & Hood 2006b;Thurgood & McLaughlin 2012;Tarr & Linton 2019;Pennicott & Cally 2021;Yadav et al 2022), but also as sources of slow, fast, and Alfvén waves (e.g., Lynch et al 2014;Karpen et al 2017;Thurgood et al 2017).…”
Section: Introductionmentioning
confidence: 99%